BIO-PROTECTIVE ACTIVITY OF GRAPE MELANIN IN RELATION TO ANTIBIOTICS (Proceedings of the YSU B: Chemical and Biological Sciences, 2024)
In this study, melanin was shown to have a bioprotective effect on lactic acid bacteria (LAB) belonging to different genera and species. In particular, melanin has been shown to increase the resistance of LAB to antibiotics. It was shown, that the effectiveness of melanin depends on the species of LAB and duration of exposure. In the case of Enterococcus faecium КE-5 and Lactobacillus rhamnosus 20-12 strains, the effectiveness of melanin is more obvious. At a concentration of 30 mg/mL, melanin reduces the cell count by 1 log unit, but it does not affect the rate of milk fermentation by LAB. In the case of two other strains, Lactobacillus acidophilus 1991 and Lactobacillus fermentum 27-2, it is less pronounced. Lactobacillus acidophilus 1991 showed the highest sensitivity, displaying high sensitivity to both the antibiotics and the indicated concentration of melanin.
Keywords: melanin; lactic acid bacteria; bioprotective agent; antibiotic